O sobreprincípio da segurança jurídica e a necessidade de sua aplicação dinâmica nos atos emanados dos poderes do Estado - Neves, Mariana Barboza Baeta (2014)
The issue of legal certainty in our system is one of the most important issues for the realization of the rights of the taxpayer in the face of state power. Had the most authoritative doctrine as a sobreprincípio spatial, legal certainty exerts integrative function of our system, interrelating with other tax constitutional principles aimed at giving effect to the set of standards that suffer its incidence. It is in this context that the quoted sobreprincípio becomes interpretive methodological vector to make sense of all the norms of law, especially in the tax case. Failure by the three branches of government (executive, legislative and judicial) the rights of the taxpayer has the legal security your greatest ally in the defense of their claims. The analysis of actual cases will demonstrate the effectiveness of this sobreprincípio should not be observed by the intensity with which it is violated, but the way in which resolved in practice mechanisms to curb violations